The Effect of Self Instruction Techniques to Reducing Academic Anxiety on Gifted Children - Hidayah, Nabila Nurul; Hasan, Hasan; Rasido, Ikhlas; Puswiartika, Dhevy (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
Gifted children have above-average intellectual abilities, but are prone to anxiety due to high demands and expectations from both their environment and themselves. This study aims to examine the effect of individual counseling using self-instruction techniques in reducing academic anxiety in gifted children at SMP GOLDEN GATE PALU. The method used was Single Subject Research (SSR) with a reversal A-B design. The results showed that after the intervention (B) through four individual counseling sessions using the self instruction technique, the average score decreased to 4.75, with a downward data trend and a change level of 3 (from a score of 6 to 3). The percentage of overlap between conditions was 25%, indicating a significant change after the intervention was given. These findings show that the self-instruction technique through positive self instruction is effective in reducing academic anxiety in gifted children.